Host Engineering for High Quantum Efficiency Blue and White Fluorescent Organic Light‐Emitting Diodes. (15th June 2015) - Song, Wook; Lee, Inho; Lee, Jun Yeob
<x xml:space="preserve">Abstract</x> High quantum efficiency in blue and white fluorescence organic light‐emitting diodes is achieved by developing a novel device architecture with fluorescent emitters doped in a thermally activated delayed fluorescent emitter as a host material.